KAJIAN SEMIOTIKA PADA KARTUN BERTEMAKAN TOLAK REKLAMASI TELUK BENOA KARYA PUTU DIAN UJIANA - Jayendra Dwi Putra (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Institut Desain dan Bisnis Bali, 2019)
Bali became one of the world's best tourism destinations. Environment and culture are still awake to make a small island nicknamed the island of this god is in great demand by the tourists. This excellence is a source of energy in driving the wheels of the economy in Bali. However, this has to sacrifice some environmental sustainability to support infrastructure in the tourism sector. Such as the conversion of land into villas, hotels and others, even today which is still a hot issue in Bali is a plan to reclaim Teluk Benoa area. This unease that makes the Balinese people began to realize the side effects of tourism progress. Balinese people are known as individuals who love the environment because they are familiar with the concept of palemahaan (good relationship with the environment). This concept is a reference community to reject the project, one of which is Dian. Dian is a cartoonist who is known to be active in the campaign against the reclamation in Teluk Benoa. His cartoon works, drafted forms that could signal a message to awaken some Balinese still expecting a reclamation project. Dian's cartoons designed as a rejection of the full reclamation of semiotics, signs and meanings. Through his cartoons, Dian not only wants to entertain through his funny display of cards, but also wants to invite and realize the Balinese people, that reclamation will not only bring financial benefits, but the dangers of environmental damage will come at any time as a side effect of the reclamation plan Tanjung Benoa.